Soeharto & barisan jendral ORBA rezim militer Indonesia 1975-1983 / David Jenkins; Penerjemah, Harsutedjo; Penyunting, Uswatul Chabibah - JENKINS, David; HARSUTEDJO; USWATUL Chabibah (Komunitas Bambu, 2010)
xi, 384 hlm. : ilus. ; 20,6 cm.